2008
DOI: 10.1177/0269881107088435
|View full text |Cite
|
Sign up to set email alerts
|

A review of the association between antipsychotic use and hyperprolactinaemia

Abstract: Recent evidence linking hyperprolactinaemia to longer-term clinical sequelae, including osteoporosis, hip fractures and possibly breast cancer, is increasing clinical awareness of the relevance of hyperprolactinaemia. A review of the literature finds clinical trials reporting some degree of comparative prolactin data among antipsychotics. Many of the randomised clinical trials (RCTs) do not report categorical rates of hyperprolactinaemia in contrast with the naturalistic studies, making it complex for clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 50 publications
11
150
1
3
Order By: Relevance
“…Olanzapine also shows little separation between 5-HT 2A RO (68-78 %) and striatal D 2 RO (85-93 %; Kessler et al 2005). These atypical antipsychotic drugs with relatively high striatial D 2 RO elevate prolactin levels (Bushe et al 2008) and can induce extrapyramidal motor side effects (extrapyramidal symptoms (EPS)) at therapeutic doses (Rummel-Kluge et al 2012). Importantly, selective 5-HT 2A receptor antagonism has been shown to enhance D 2 -receptor-antagonist-mediated antipsychotic efficacy while reducing motor side effects and hyperprolactinemia in animal models (Gardell et al 2007; Wadenberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Olanzapine also shows little separation between 5-HT 2A RO (68-78 %) and striatal D 2 RO (85-93 %; Kessler et al 2005). These atypical antipsychotic drugs with relatively high striatial D 2 RO elevate prolactin levels (Bushe et al 2008) and can induce extrapyramidal motor side effects (extrapyramidal symptoms (EPS)) at therapeutic doses (Rummel-Kluge et al 2012). Importantly, selective 5-HT 2A receptor antagonism has been shown to enhance D 2 -receptor-antagonist-mediated antipsychotic efficacy while reducing motor side effects and hyperprolactinemia in animal models (Gardell et al 2007; Wadenberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…When evaluating hyperprolactinaemia it is also critical to understand the incidence or prevalence of hyperprolactinaemia from the patient perspective as opposed to a mean level from a cohort. Recent data are now tending to more commonly include both variables (Mackin et al, 2011) whereas in our 2008 review of this topic we reported that though 60% of studies reporting prolactin data included some degree of categorical analysis, this was seen mainly in the naturalistic studies (88%) rather than the randomised controlled trials (42%) (Bushe et al, 2008). …”
Section: Measurement Of Prolactin and Definition Of Hyperprolactinaemiamentioning
confidence: 90%
“…Conversion rates from ng/ml to mIU/L are not standardised and vary between 21.2 and 36 dependent on the assay employed (Bushe et al, 2008). Furthermore, clinical reports do not always report either the normal range utilised or sometimes the units of measurement (McEvoy et al, 2007).…”
Section: Measurement Of Prolactin and Definition Of Hyperprolactinaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotic related hyperprolactionemia incidences have been reported to range from 42 to 93% for women and 18 to 72% for men (6). The paliperidone, active metabolites of risperidon and amisulpride, and risperidon's itself are known to cause hyperprolactinemia (7).…”
mentioning
confidence: 99%